Lucia Cecchet, Poverty in Athenian Public Discourse. From the Eve of the Peloponnesian War to the Rise of Macedonia (=Historia Einzelschriften 239), Stuttgart, Franz Steiner Verlag, 2015, pp. 283 [ISBN: 978-3-515-11160-7]. - Fernández Prieto, Aida (Gerión. Revista de Historia Antigua, 2020)
Reseña del libro de Lucia Cecchet, Poverty in Athenian Public Discourse. From the Eve of the Peloponnesian War to the Rise of Macedonia (=Historia Einzelschriften 239), Stuttgart, Franz Steiner Verlag, 2015, pp. 283 [ISBN: 978-3-515-11160-7].